POTRAYING STUDENTS’ LANGUAGE PROBLEMS IN COMPREHENDING NARRATIVE READING TEXT - Alviaderi Novianti; Windi Kurniawati (English Education Department of STKIP Pasundan, 2021)
This research aimed at recognizing language problems faced by the students in comprehending narrative reading text. The investigation includes the students’ language problems and the teachers’ solution regarding to his students’ language problems while comprehending narrative reading text. This research was carried out in one of Junior High School in Bandung and involved 20 students as research sample. In gaining the research data, the writers used several instruments including observation sheets, semi structured interview questions for both students and teacher, and a set of narrative reading comprehension test. The finding showed the students were poor in vocabulary, pronunciation, difficulties search about character in the text, difficulties search about generic structure in the text, difficulties search a moral value in the text, difficulties in answering the reading comprehension question. In addition, the finding of interview data showed solution for those problems were that teacher used teacher give particularly in reading skill comprehension and do repetition to give the mean of the words and then give the students clues for some information and make the students create map-brain.